Distribution of ESBLs among Escherichia coli isolates from outpatients with recurrent UTIs and their antimicrobial resistance - Sareaa Al-Mayahie; Jaafar JH Al Kuriashy (Journal of Infection in Developing Countries)
Introduction: Extended-spectrum β-lactamase (ESBL)-producing strains of Enterobacteriaceae are considered to be emerging pathogens. They are a major problem in hospitalized as well as community-based patients. Major outbreaks involving ESBL strains have been reported from all over the world. Recurrent urinary tract infection (UTI) is one of the risk factors for infection with ESBL-producing E. coli in hospitalized and non-hospitalized patients. Methodology: Ninety-one E. coli isolates from outpatients with recurrent UTIs were surveyed phenotypically and genotypically for ESBL production and tested for antimicrobial susceptibility. Results: Of 91 E. coli isolates, 75.8% were resistant to each of cefotaxime and ceftazidime and 74.7% produced ESBLs. CTX-M-type was the most frequent ESBL (accounting for 70.3%), with CTX-M-1 being the only subtype possessed by these isolates. The prevalence of OXA- and SHV-type was 32.9% and 10.9%, respectively. None of the isolates produced TEM β-lactamase. All OXA-type ESBL were produced concomitantly with CTX-M1. Both ESBL producers and non-producers had high resistance to ampicillin followed by trimethoprim-sulphamethoxazole, third-generation cephalosporins, and tetracycline. No isolate showed resistance to imipenem and meropenem. In total, resistance rates of ESBL producers were higher than those of ESBL non-producers, as was multidrug resistance (52.7% versus 8.7%, respectively). Conclusions: Our study documented high distribution of ESBLs among E. coli isolates from outpatients with recurrent UTIs, with CTX-M as the predominant ESBL. In the current situation, it is important that antibiotic treatment is be started only after a proper sensitivity report is obtained from the laboratory.